ANALISIS FAKTOR PENYEBAB KECELAKAAN TRUK DI INDONESIA MENGGUNAKAN PENDEKATAN HUMAN FACTORS ANALYSIS AND CLASSIFICATION SYSTEM (HFACS) - Handriansah, Riki
The truck accidents in Indonesia pose a serious safety threat. This is indicated by the increasing number of cases and the devastating impact. This research aims to delve into the factors causing truck accidents in Indonesia through a comprehensive analysis using the Human Factors Analysis and Classification System (HFACS) approach. Additionally, statistical odds-ratio testing is employed to evaluate the interrelationships among factors based on the Contributory Factors Interaction Model (CFIM), along with testing the relationships of accident characteristics. The data utilized encompasses 120 news investigations of truck accidents that occurred in Indonesia from January 2022 to May 2023. The analysis results indicate that unsafe behaviors contribute the most to accidents (35%), followed by outside factors at 32%, precondition for unsafe behaviors at 20%, and both unsafe supervision and organizational influences each at 7%. Furthermore, the analysis of accident risk factors using the framework from the National Academy of Sciences, Engineering, and Medicine (NASEM) reveals that trucks factors rank highest as the risk factors for truck accidents in Indonesia. Based on the odds-ratio statistical test, it was found that latent failure category factors can influence active failure, and some latent failure factors can influence each other. As for testing the relationship of characteristics, it was found that class II trucks have a lower chance of having an accident with more than one vehicle involved or causing more than one death compared to other class trucks. Single accidents also have a lower chance of causing more than one fatality compared to accidents with more than one vehicle. From this study, it can be concluded that truck accidents in Indonesia are caused by unsafe behavior factors which can be influenced by outside factors and preconditions for unsafe behaviors. The government together with the company can design policies and preventive measures that focus on these factors, so that it will potentially reduce the number of truck accidents that occur in Indonesia.